Interaksi Antar Dua Komunitas Agama (Islam-Kristen) Pasca Konflik di Desa Latta Kota Ambon - Alce Albartin Sapulette (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2018)
Latta Village is one of the villages besides Wayame Village which did not experience the impact of the Maluku conflict in 1999, even though the people were multi-religious (Islam and Christian). The people of Latta Village remain united and maintain the common life order between Islam and Christianity that has been fostered from the beginning. Relationships or social relations remain well intertwined with one another. Research has been conducted on the interaction between two religious communities (Islam-Christians) post-conflict in Latta Village, Ambon City. This study aims to describe the social interactions that occur in the community using a qualitative approach. Based on the results of the study, it was found that there was an interaction relationship that remained intertwined in the lives of the people of Latta Village before and after the conflict. The relationship occurred because of good contact and communication between the Islamic community and the Christian community, and also because of the intervention of the Village Head, Imams, Priests and the community as a whole. Therefore, it can be concluded that the interaction relationships must remain maintained in order to create a life of a peaceful and harmonious society.Keywords: social interaction, religious community,conflict